Effect of particle size of variolls energy and protein sources on hardness Rnd setting time of urea-molasses mineral lick blocks - SIHAG, ZILE S; CHAHAL, S M; PUNIA, B S (The Indian Journal of Animal Sciences, 2014)
Experiments were conducted to study the hardness and setting time of urea molasses mineral block (UMMB) formulated from 4 energy sources (deoiled rice bran, maize, barley, wheat bran), 3 protein sources (mustard-cake, groundnut-cake, sunflower-cake), 4 particle sizes (coarse, medium, fine, mixture) and 4 molasses levels (45, 50, 55, 60%), in a 4x3x4x4 factorial design. Hardness of blocks decreased (P<0.05) from 0.9968 to 0.2091 kg/cm2 as the level of molasses increased from 45 to 60%. Increase in particle size from fine to coarse decreased (P<0.05) the hardness of blocks from 0.8780 to 0.3219 kg/cm2. At 45% molasses level, mixing was very poor with mixture, medium and fine particles of various energy and protein sources. Even at 50% molasses level mixing was poor with fine particles of various energy and protein sources. Setting time of UMMB increased from 0 to 24-48 hr and more with the increase of molasses. The maximum hardness (2.03 kg/cm2 ) was achieved with groundnut-cake and maize ground through a hammer mill having sieve size 4 mm at 45% molasses levels. At 50% molasses level, maximum hardness was 1.99 kg/cm2 with medium particles of deoiled rice bran and mustard-cake and lit 55% molasses level the maximum hardness (1.12 kg/cm2 ) was obtained with fine particles of wheat bran and sunflower-cake. Results indicated that molasses level and particle size of various energy and protein sources affected the hardness and setting time of urea molasses mineral blocks.